Does the presence of hepatitis virus B and C influence the evolution of diffuse large B-cell lymphoma?. Issue 6 (June 2015) - Rubio, Judit; Franco, Fernando; Sánchez, Antonio; Cantos, Blanca; Méndez, Miriam; Calvo, Virginia; Maximiano, Constanza; Perez, David; Millán, Isabel; Sánchez-Beato, Margarita; Provencio, Mariano
Abstract Hepatitis infection has a high prevalence in patients with non-Hodgkin lymphoma. Our objective was to evaluate clinical characteristics and survival of patients diagnosed with diffuse large B-cell lymphoma (DLBCL) who were hepatitis B and/or C (HBV/HCV) positive. We reviewed 224 patents diagnosed with DLBCL and found 21 to be HBV/HCV positive (9.3%). Significant differences were found in the number of nodal regions affected, four in HBV/HCV positive versus two in virus negative patients, and in liver involvement, which was greater in HBV/HCV positive patients (28.6% vs. 10%, p = 0.028). No significant differences were found in the two groups with respect to the number of relapses or the probability of overall or progression-free survival. Despite the finding of differences with respect to stage, total number of nodal regions affected and liver involvement, HBV/HCV positive and negative patients with DLBCL should receive the same treatment, and the disease responds and evolves equally.